Age of patients undergoing surgery. Issue 8 (22nd May 2019) - Fowler, A J; Abbott, T E F; Prowle, J; Pearse, R M
Abstract: Background: Advancing age is independently associated with poor postoperative outcomes. The ageing of the general population is a major concern for healthcare providers. Trends in age were studied among patients undergoing surgery in the National Health Service in England. Methods: Time trend ecological analysis was undertaken of Hospital Episode Statistics and Office for National Statistics data for England from 1999 to 2015. The proportion of patients undergoing surgery in different age groupings, their pooled mean age, and change in age profile over time were calculated. Growth in the surgical population was estimated, with associated costs, to the year 2030 by use of linear regression modelling. Results: Some 68 205 695 surgical patient episodes (31 220 341 men, 45·8 per cent) were identified. The mean duration of hospital stay was 5·3 days. The surgical population was older than the general population of England; this gap increased over time (1999: 47·5 versus 38·3 years; 2015: 54·2 versus 39·7 years). The number of people aged 75 years or more undergoing surgery increased from 544 998 (14·9 per cent of that age group) in 1999 to 1 012 517 (22·9 per cent) in 2015. By 2030, it is estimated that one-fifth of the 75 years and older age category will undergo surgery each year (1·49 (95 per cent c.i. 1·43 to 1·55) million people), at a cost of €3·2 (3·1 to 3·5) billion. Conclusion: The population having surgery in England is ageing at a faster rate than the general population. Healthcare policies must adapt to ensure that provision of surgical treatments remains safe and sustainable. Graphical Abstract: The surgical population of England is ageing more quickly than the general population. More than 1·4 million patients aged over 75 years will have surgery each year by 2030. Worrying prediction